Early-stage study on the urgency of a sport climbing performance assessment model based on LTAD framework for talent identification - Sukiyandari, Liska; Setyawati, Heny; Rahayu, Tandiyo; Sulaiman, Sulaiman; Ariyatun, Ariyatun (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the urgency of developing a Sport Climbing Performance Assessment (SCPA) model based on the Long-Term Athlete Development (LTAD) framework for talent identification. A quantitative descriptive approach was employed, with data collected through a structured questionnaire distributed to 22 respondents, including head coaches, assistant coaches/administrators, and sports science experts. The analysis involved descriptive statistics, Shapiro-Wilk normality tests, reliability testing, and One-Way ANOVA to explore differences in perception among participant groups. The results indicated a strong consensus among respondents on the need for a structured and LTAD-oriented performance assessment model for sport climbing. Overall, participants showed high levels of agreement on the urgency of establishing a more systematic and long-term development framework. While most group comparisons revealed no significant perceptual differences, one area showed head coaches expressing notably stronger expectations for model development than other groups. In conclusion, there is a broadly shared recognition of the need to reform current athlete selection methods by incorporating objective and developmentally appropriate performance assessments. The study supports the foundation for constructing a more adaptive, standardized, and scientifically grounded SCPA model. From a practical standpoint, these findings highlight the importance for sport governing bodies to implement long-term, inclusive assessment systems that align with diverse coaching perspectives and promote consistent athlete development.